2014
DOI: 10.5005/jp-journals-10006-1278
|View full text |Cite
|
Sign up to set email alerts
|

Single Step Test for Diagnosing Gestational Diabetes Mellitus

Abstract: Gestational diabetes mellitus is one of the most common medical disorders found in pregnancy. Clinical recognition of GDM is important because timely intervention by dietary measures or insulin and fetal surveillance can reduce the well described associated maternal and fetal complications. This observational study was done in PGIMS, Rohtak during period from January 2011 to December 2011. Single step test using 75 gm oral glucose was used as screening and diagnostic test for GDM. Fetomaternal outcome was stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Eleven studies reported the distribution of GDM diagnosed by gestational age [18, 26, 30, 32, 37, 39, 41, 47, 52, 56, 61]. Six studies reported the percentage of total GDM cases diagnosed in the first trimester, which ranged from 11 to 60% (Appendix S11) [18, 26, 39, 41, 47, 56].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven studies reported the distribution of GDM diagnosed by gestational age [18, 26, 30, 32, 37, 39, 41, 47, 52, 56, 61]. Six studies reported the percentage of total GDM cases diagnosed in the first trimester, which ranged from 11 to 60% (Appendix S11) [18, 26, 39, 41, 47, 56].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies reported the percentage of total GDM cases diagnosed in the first trimester, which ranged from 11 to 60% (Appendix S11) [18, 26, 39, 41, 47, 56]. Six studies reported the percentage of total GDM cases diagnosed before 24 weeks of gestation, which ranged from 27.5 to 54.55% [26, 30, 32, 37, 52, 61].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in a prospective study 20 (cases: n ¼ 35; controls: n ¼ 465), 11.4% (n ¼ 4) of the sample had their diagnosis in the initial 16 weeks, and 88.6% (n ¼ 31), in 24-28 weeks. 20,21 Miranda et al, 22 in a case-control study (cases: n ¼ 201; controls: n ¼ 201), found hypoglycemia at birth to be the most frequent complication of GD, and identified hypoglycemia and RDS as important causes of neonatal morbidity; in relation to the birth weight of the NBs, there were no statistical differences. In the present study, the mean birth weight and rate of neonatal hypoglycemia were significantly higher in infants of mothers with GD, and, when considering RDS, the same did not occur in the study by Miranda et al 21 The lower rate of RDS in our study was possibly associated with the fact that most deliveries occurred at term, with lesser chance of problems related to delayed pulmonary maturity.…”
Section: Discussionmentioning
confidence: 96%
“…20,21 Miranda et al, 22 in a case-control study (cases: n ¼ 201; controls: n ¼ 201), found hypoglycemia at birth to be the most frequent complication of GD, and identified hypoglycemia and RDS as important causes of neonatal morbidity; in relation to the birth weight of the NBs, there were no statistical differences. In the present study, the mean birth weight and rate of neonatal hypoglycemia were significantly higher in infants of mothers with GD, and, when considering RDS, the same did not occur in the study by Miranda et al 21 The lower rate of RDS in our study was possibly associated with the fact that most deliveries occurred at term, with lesser chance of problems related to delayed pulmonary maturity. 22 The proportion of cesarean sections in the present study was similar to that found in a retrospective cohort study 22 with women with GD diagnosis (n ¼ 703) in a hospital in the city of Joinville, Southern Brazil: 52.2% (n ¼ 367) had cesarean sections as the delivery route.…”
Section: Discussionmentioning
confidence: 96%